Metaphysics, Elemental Transformation, Medicine: A Specimen of Avicenna’s System of Thought in Ms. Escorial 621 - Bertolacci, Amos (Oriens, 2019)
Abstract The present article brings to the scholarly attention the Avicennian manuscript San Lorenzo de El Escorial (Madrid), Real Biblioteca del Monasterio de San Lorenzo de El Escorial, 621, by conveying a basic description of its codicological features and by locating it in the wider context of the connection metaphysics-medicine that the transmission of Avicenna’s magnum opus Kitāb al-Šifāʾ (Book of the Cure/Healing) displays. The manuscript at stake is the only extant, though incomplete, codex of the Ilāhiyyāt (Science of Divine Things) of Avicenna’s Šifāʾ presently known in the Iberian peninsula (Spain and Portugal), and one of the few codices of the Šifāʾ housed there. In its present state, it cumulates metaphysics and medicine, since it joins some excerpts of the Ilāhiyyāt with fragments of the commentaries on Avicenna’s Al-Qānūn fī l-ṭibb (Canon of Medicine) by Ibn al-Nafīs al-Qurašī (d. 687 H/1288) and by Quṭb al-Dīn al-Šīrāzī (634–719 H/1236–1311). The part of the commentary on Avicenna’s Canon by Ibn al-Nafīs al-Qurašī preserved in this manuscript contains a revealing critical quotation of a medical tenet which Avicenna discusses in the Šifāʾ; this criticism very likely represents an instance of the ‘rectification’ of Avicenna’s philosophical encyclopedia of which Ibn al-Nafīs is credited in historical sources. The example of the revision of Avicenna’s philosophy by Ibn al-Nafīs analyzed on the basis of this manuscript makes clear that physicians in the XIII century did not limit their familiarity with Avicenna’s works to the Canon of Medicine and the other medical works of Avicenna, but adopted some kind of all-encompassing approach to Avicenna’s oeuvre, which did not eschewed tackling critically also the Šifāʾ on the basis of a profound and extensive knowledge of the Šayḫ al-raʾīs’s philosophical masterpiece.